Расчет постоянных распространения Н01-волны в кольцевом волноводе с конечной толщиной колец - Масалов, С.А. (Radiotekhnika, 1966)
Расчет постоянных распространения Н01-волны в кольцевом волноводе с конечной толщиной колец